Desafios e possibilidades do Pibid : uma análise das práticas docentes em educação ambiental de educadoras/es em formação inicial dos cursos de biologia e de educação física da Unesp de Rio Claro - Tibúrcio, Gabriela Santos (2016)
The central aim of this research was contribute to the construction of knowledge about teaching practices used by a group associated to the Institutional Program of Teaching Initiation Scholarship (Pibid) of the Universidade Estadual Paulista "Júlio de Mesquita Filho" (Unesp). In order to evidence real and viable conditions for the elaboration and execution of environmental education practices and interdisciplinarity by basic schools’ teachers we sought to approach them to the realities of the public school. The research included the participation of undergraduate students of biological sciences course (former scholar of the program), and an elementary school science teacher. The research has been developed from the communicative-critical methodology guidelines. In the first article, as collection procedure, we analyze documents with specific aim of reflect about the current conjuncture of teachers training in Brazil. These documents were: reports issued by Capes, the subproject notice of Pibid group in question and documents produced by the group throughout the realization of the projects. In other articles, were conducted communicative discussion groups, based on the intersubjectivity arising from the collective reflection of the participating people as collective procedure. The analysis of the research sought to identify potentially transformative elements and potentially barriers’ elements to the themes of research – interdisciplinarity (article 2), environmental education (article 3) and teachers training (article 4) – in order to understand limits and possibilities of each one of them in the context of Brazilian public school. As main results, we identified real and viable possibilities of interdisciplinary practices and environmental education practices, in a critical perspective, in the scholar context from the articulation between initial and continuing teachers training, in a proposal for collective work. Moreover, the results showed the importance of work in this perspective throughout the formative process of teachers and, accordingly, we consider the Pibid as highly relevant program for critical teachers training and, in this direction, we emphasize the importance of the fight for public policies that enhance the teaching career.